Towards successful participation in academic writing: What can we learn from assessment - Shalem, Y.; Dison, L.; Reed, Y. (South African Journal of Higher Education, 2016)
The main aim of this short introductory article is to provide a context for the three articles that follow. It begins with a brief review of literature pertinent to student success or failure in the academy and then moves to a description of the background of a research project, which investigated the cognitive and academic literacy demands of formative and summative assessment tasks for first-year students in the Bachelor of Education (Bed) programme of the School of Education at the University of the Witwatersrand (WSoE).